Canine visceral leishmaniasis: Relationships between clinical status, humoral immune response, haematology and Lutzomyia (Lutzomyia) longipalpis infectivity - da Costa-Val, Adriane Pimenta (Vet J, 2007)
The main source of Leishmania infantum infection in humans is a naturally infected dog. This study reports on the infectivity to phlebotomine sandflies (Lutzomyia longipalpis) of serologically positive mongrel dogs that differed in clinical status, haematology and humoral responses to immunoglobulin (Ig) G(T) (total anti-Leishmania IgG), IgG(1) and IgG(2) subclasses of antibody to crude antigen of L. infantum. Forty-five female L. longipalpis were allowed to feed directly on the ears of dogs classified as asymptomatic, oligosymptomatic or symptomatic before being dissected five days later. Promastigotes were detected in 88% of the dissected sandflies. The highest rate of infectivity to sandflies was found in symptomatic dogs, followed by oligosymptomatic and asymptomatic animals. The results suggest that dogs naturally infected with L. infantum with higher total IgG and IgG(2) concentrations and lower haematocrit levels were able to infect the highest proportion of L. longipalpis. No correlation was observed between anaemia and the intensity of clinical signs. Symptomatic dogs presented the highest infection rate and intensity of infection.